ANALISIS STRUKTUR BAWAH PERMUKAAN GUNUNG IJEN BANYUWANGI - Ahmad Nor Hamidy; Ashila Juan Fortuna; Imelda Mar'ata Sholih; Revinda Oktavia; Rabiah Al'Adawiyah; Firdha Kusuma Ayu Anggraeni; Sri Astutik (JURNAL PEMBELAJARAN FISIKA, 2022)
Analysis of the subsurface structure of Mount Ijen, Banyuwangi was carried out based on anomaly data obtained from satellite image data. This research was conducted with the aim of identifying the subsurface structures around the research site. In this study, what is determined is the complete Bouguer anomaly (ABL), regional and residual anomalies based on the ABL, and their inversion modeling. The results of the representation of underground structures based on residual anomalies obtained from complete and regional Bouguer anomaly data. The complete bouguer anomaly values obtained in the Mount Ijen area range from 12.2 to 110.7 mGal. In the process of separating regional and residual anomalies, different anomaly values are produced. The regional anomaly value ranges from +12.2 to +110.7 mGal while the residual anomaly ranges from -4.2 to +2.4 mGal